Wpływ zmian w działaniach marketingowych firm na zachowania konsumentów w czasie pandemii COVID-19 - Młynarczyk, Justyna; Parcheta, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
There are many elements, which appeal to the buyers’ shopping preferences and advertising can undoubtedly be considered as one of them. Over the years, its new forms have been noticeable as a result of the prevailing trends or forecasts. However, the emergence of a new and unknown situation related to the pandemic outbreak made companies look for new solutions. The aim of this article is to discuss the changes which were observed in company marketing activities during the COVID-19 pandemic, as well as their impact on customer behaviour and preferences. The study was carried out using a questionnaire. Based on the results, a small number of respondents supported ceasing promotion during the pandemic. Additionally, it is worth noting that most of them agreed with the statement that advertising should be changed and adapted to the gravity of the current situation.
Keywords: advertising; customer behaviour; shopping preferences; COVID-19